Altered gut microbiome composition and tryptic activity of the 5xFAD Alzheimer’s mouse model - Brandscheid, Carolin; Schäfer, Karl Herbert (Journal of Alzheimer's disease, 2017)
The regulation of physiological gut functions such as peristalsis or secretion of digestive enzymes by the central nervous system via the Nervus vagus is well known. Recent investigations highlight that pathological conditions of neurological or psyc